Molecular statics simulations of ferroelectric barium titanate in the rhombohedral phase - Endres, Florian; Steinmann, Paul (GAMM-Mitteilungen, 2015)
Ferroelectric functional materials improved tremendously over the last decades. Therefore not only the material science regarding material manufacturing but also simulation models and algorithms have been developed further. There are two fundamentally different types of models available. Firstly, particle based models describe material as a discrete particle system. Secondly, continuum mechanics describe material as a continuum. Both continuum mechanics and the particle based methods have their benefits and disadvantages. Still the main disadvantage of particle based methods are the enormous computational costs. In this work the fundamentals of a molecular statics algorithm for the simulation of ferroelectric functional materials are elucidated in order to reduce the computational costs. Furthermore barium titanate has been simulated in order to demonstrate the applicability of the molecular statics algorithm. Since the computational costs of molecular statics are highly reduced compared to other atomistic algorithms larger systems can be calculated more efficiently.
Keywords: Molecular statics; barium titanate; core-shell model; ferroelectric materials